BAHASA ASING DALAM ALQURAN : (Analisis Kritis atas Pemikiran Arthur Jeffery) - Sulkifli; Abd Rajab; Nurhenna Aina (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2023)
The objective of this article is to examine and analyze Arthur Jeffery's thoughts on the Qoran. This research is qualitative research with a literature review. Arthur with his philological method, analyzes the foreign languages (non-Arabic) contained in the Quran, at least he found around 316-317 foreign languages adopted by the Prophet in the Quran, as stated in his book entitled “The Foreign Vocabulary of The Quran”. Various accusations directed by Arthur to discredit and weaken the religion of Islam have raised doubts about this divine revelation. The results of this study indicate that the accusations made by Arthur about the existence of foreign words and the Prophet Muhammad who has been influenced by previous religions, such as Judaism and Christianity mostly use prejudice and mere assumptions and do not present scientific analysis data with evidence of historical studies and data as reinforcement for his argument.